Peran Teknologi Radio terhadap Efektivitas Komunikasi Operasional dan Kualitas Layanan PT Mobilkom Telekomindo - Jeneva Augustin; Lola Maharani (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study analyzes the role of radio technology in improving operational communication effectiveness, occupational safety, and service quality at PT Mobilkom Telekomindo. The study employed a descriptive qualitative approach with data collected through observation, semi-structured interviews, and documentation during an internship period from April to May 2026. The informants were selected purposively and consisted of a supervisor, HSSE officer, operational analyst, and field technician/crew. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing, along with source triangulation to ensure data validity. The findings show that radio technology plays an important role in accelerating information delivery, improving multipoint coordination among teams, enabling real-time work monitoring, and supporting faster operational decision-making. In addition, radio communication contributes to the implementation of safety procedures and emergency response, thereby minimizing the risk of workplace accidents. However, several challenges were identified, including noise interference, limited signal coverage in certain areas, device damage, limited battery capacity, and human error in usage. PT Mobilkom Telekomindo has implemented mitigation efforts through routine maintenance, provision of backup batteries, and improved understanding of communication procedures. Thus, radio technology remains an effective and relevant communication tool in supporting operational effectiveness and improving service quality at PT Mobilkom Telekomindo.